Management of MSME Education and Training Programs at the Department of Cooperatives and Small Enterprises, West Java - Assifa Nuradiesti; Reni Wijayanti; Nur Imam Taufik (Trescode Green Organization, 2025)
This study examines the administrative management of micro, small, and medium enterprise (MSME) education and training programs implemented by the Regional Technical Implementation Unit for Cooperative and Entrepreneurship Education and Training (UPTD P3W) under the Department of Cooperatives and Small Enterprises of West Java Province. The study was conducted through a five-month internship placement from August to December 2025, during which the intern participated directly in administrative activities guided by three competency units of the 2024 Indonesian National Work Competency Standard (SKKNI) for Professional Administration: preparing meeting minutes, developing training presentation materials, and assisting with the organization of institutional events. Data were collected through direct participation, documentation, and a daily activity logbook, then analyzed descriptively against each competency's performance criteria (KUK). The results show that the intern completed 101 recorded work activities, dominated by event and training-schedule coordination, particularly the province-wide Koperasi Desa Merah Putih (Red-and-White Village Cooperative, KDMP) training program that involved 217 instructors and roughly 11,000 participants across five regions of West Java. Most performance criteria were fulfilled, although meeting-minute concept approval and presentation-template standardization were not yet optimally implemented. The study concludes that administrative competencies can be effectively practiced through structured internship placements and offers recommendations to strengthen documentation systems, scheduling coordination, and task-delegation practices within the training unit.